Recent advances in heat and water management of forced-convection open-cathode proton exchange membrane fuel cells. (September 2022) - Xing, Shuang; Zhao, Chen; Zou, Jiexin; Zaman, Shahid; Yu, Yang; Gong, Hongwei; Wang, Yajun; Chen, Ming; Wang, Min; Lin, Meng; Wang, Haijiang
Abstract: Forced-convection open-cathode proton exchange membrane fuel cells (FCOC-PEMFCs) can directly use ambient air to supply oxygen and provide cooling without a complex air supply subsystem, have drawn tremendous attention. However, inefficient heat and water management are challenging in FCOC-PEMFCs. This paper aims to provide the general idea and current idea from component level to system level for the design of heat and water management of FCOC-PEMFCs. The water-heat-electric characteristics of FCOC-PEMFCs, the influence of operating conditions, the flow channel design at the single-cell level, the application of novel heat dissipation enhancement methods at the stack level, the design of the cooling subsystem, and temperature control strategy are deeply analyzed. Besides, the key findings, challenges, and future work are put forward. The future work mainly includes the enhancing the environmental adaptability and stability of the stack, avoiding flooding and dehydration, combining passive and active methods to enhance heat and water management ability, developing efficient temperature control strategies based on a large number of experimental data and machine learning technology, and diagnostic technology applicable for FCOC-PEMFC. The provided information is anticipated to accelerate the commercialization of portable fuel cells. Highlights: Heat and water management of forced-convection open-cathode PEMFCs was reviewed. Heat-water-electricity characteristics of FCOC-PEMFCs were analyzed. Cooling subsystem designs and temperature control strategies were stated. Enhancement methods of heat and water management of FCOC-PEMFCs were summarized. Future research directions of FCOC-PEMFCs were presented.